Acetic Acid-Producing Endophyte Lysinibacillus fusiformis Orchestrates Jasmonic Acid Signaling and Contributes to Repression of Cadmium Uptake in Tomato Plants - Zhu, Lin; Guo, Jiansheng; Sun, Yujun; Wang, Songhua; Zhou, Cheng (Frontiers in Plant Science, 2021)
Diverse signaling pathways regulated by phytohormones are essential for the adaptation of plants to adverse environments. Root endophytic bacteria can manipulate hormone-related pathways to benefit their host plants under stress conditions, but the mechanisms underlying endophyte-mediated plant stress adaptation remain poorly discerned. Herein, the acetic acid-producing endophytic bacteria Lysinibacillus fusiformis Cr33 greatly reduced cadmium (Cd) accumulation in tomato plants. L. fusiformis led to a marked increase in jasmonic acid (JA) content and down-regulation of iron (Fe) uptake-related genes in Cd-exposed roots. Accordantly, acetic acid treatment considerably increased the JA content and inhibited root uptake of Cd uptake. In addition, the Cr33-inoculated roots displayed the increased availability of cell wall and rhizospheric Fe. Inoculation with Cr33 notably reduced the production of nitric oxide (NO) and suppressed Fe uptake systems in the Cd-treated roots, thereby contributing to hampering Cd absorption. Similar results were also observed for Cd-treated tomato plants in the presence of exogenous JA or acetic acid. However, chemical inhibition of JA biosynthesis greatly weakened the endophyte-alleviated Cd toxicity in the plants. Collectively, our findings indicated that the endophytic bacteria L. fusiformis effectively prevented Cd uptake in plants via the activation of acetic acid-mediated JA signaling pathways.